Critical Reflections and contributions to a Physical Education Specialist Students practice’s program - Lucio Martínez Alvarez; Juan Mañeru Cámara; Henar Rodriguez Navarro (Revista Electrónica Interuniversitaria de Formación del Profesorado)
This work is part of a bigger strategy of participative investigation-action focused on critical reflection and improvement of a Practicum program for Physical Education specialist teachers. We liked to know which were the worries expressed by the student teachers before entering the school settings, with the intention of reflecting on how the program recognizes, integrates and answers to the emotional dimension of the Practicum.In that way, there were categorized and analyzed the writings and questionnaires the students (N 54) elaborated in the preparatory phase of the Practicum of the course 08-09. Later, we contrasted these with the intentions, actions, and strategies the programmed had planned for attending the emotional dimension that arises in this stage of the practicum.In doing so, we were in better disposition to check the coherence of the programme, the principles sustaining it, and the degree which it responds to the human and social context where it is developed, so we were able to fine tune the programme, aware of the emotional dimension of the Practicum.